Community-Based Intervention as a Strategy for Overcoming and Preventing Childhood Stunting - Qory Tifani Rahmatika; Sigit Mulyono (Jurnal Kesehatan, 2021)
Stunting is identified as an indicator of growth failure in the first 1000 days of the child and is a major nutritional problem that can affect the productivity and human resources of a nation in the future. Community-based interventions are considered as an effective strategy to overcome the challenges of accelerating stunting reduction and are considered capable of promoting healthy behaviors and having a positive impact on health degrees in a wider population. The purpose of this literature study is to provide an overview of community-based interventions as an effort to prevent and accelerate the decline in stunting rates in Indonesia. The method used was literature studies using online databases sources such as Proquest, Science Direct, and Wiley. From the literature searching, it was obtained 9 research articles which were published in the range of 2011-2021. In general, the results of this literature study classify several community-based interventions that have been successfully implemented into 4 (four) focus intervention objectives; interventions that focus on improving nutrition, interventions that focus on improving adequate care and parenting patterns, interventions to address environmental sanitation problems, and interventions to improve health status. Community-based interventions which were chosen to be implemented in the studies are able to decrease the stunting rates in toddles using different types of strategies. It requires strong involvement and commitment from all elements in the community including health workers, communities, and actors in the community in implementing community-based intervention strategies in overcoming the stunting problem.